2022
DOI: 10.1111/aphw.12341
|View full text |Cite
|
Sign up to set email alerts
|

Online Isha Upa Yoga for student mental health and well‐being during COVID‐19: A randomized control trial

Abstract: College students experienced increased stress and anxiety during the COVID‐19 pandemic. This study evaluated the effect of brief online Isha Upa Yoga modules on undergraduates' mental health and well‐being. Randomized control trial (RCT) with waitlist control crossover (N = 679). The intervention group was instructed to learn and practice the modules daily for 12 weeks. At the end of the 4‐week RCT, the control group was instructed to learn and practice the modules for the remaining 8 weeks. Primary outcomes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 52 publications
4
32
0
2
Order By: Relevance
“…Next, a closer look at compliant participant scores in the cohort with brief exposure to yoga intervention (Simha Kriya) revealed a sustained improvement in PSS scores at week 6 and week 12 compared to non-compliant participants. These findings agree with those reported by Chang et al (33) in a waitlisted RCT in college students during the pandemic. They reported that consistent practice of yoga for 3 or more times per week resulted in significant changes in stress, anxiety, depression, wellbeing, resilience, positive & negative affect scores.…”
Section: Discussionsupporting
confidence: 93%
“…Next, a closer look at compliant participant scores in the cohort with brief exposure to yoga intervention (Simha Kriya) revealed a sustained improvement in PSS scores at week 6 and week 12 compared to non-compliant participants. These findings agree with those reported by Chang et al (33) in a waitlisted RCT in college students during the pandemic. They reported that consistent practice of yoga for 3 or more times per week resulted in significant changes in stress, anxiety, depression, wellbeing, resilience, positive & negative affect scores.…”
Section: Discussionsupporting
confidence: 93%
“…All incorporated studies assessed the effectiveness of internet-based psychological intervention programs for reducing stress, anxiety, and depression among university students during COVID-19 social distancing. Seven studies were conducted by researchers in American universities [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ], two studies in Asian universities [ 39 , 40 ], and one study in an African university [ 41 ]. Meta-analyses were performed separately on interventions for reducing stress, anxiety, and depression ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The average number of sessions of the included mental interventions was 15.3 sessions, while the length of sessions varied between 10 and 90 min. The duration of the interventions also varied greatly, ranging from three weeks [ 40 ] to twelve weeks [ 32 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations